A Total systems design study on ACR Furniture Manufacturing Corp. - Banda, Lota B.; Domingo, Gay R.; Garcia, Blessie Marie T.; Santos, Josephine C. (College of Engineering, 2002)
ACR Furniture Manufacturing Corporation (ACRFMC) since its establishment in 1978 has produced its own line of furniture and home furnishing products. It has been supplying large department stores, hotels, and regional distributors with furniture, beds and all kinds of home furnishings which cater to different market segments. However, as most of the domestic furniture manufacturers in the country, ACR faces different challenges with respect to its product quality, production capabilities, satisfying customer need on time and in full, as well as other problems that need to be addressed to stay competitive in the industry. In light of this, a total systems design study is performed on ACRFMC. The entire study consists of three stages. First, a thorough documentation of the system is performed, taking into consideration the occurrence of the above mentioned challenges in furniture manufacturers. The second stage is an assessment of the strengths, weaknesses, opportunities and threats that the company is experiencing or is perceived to apply to the company in the near future using the SWOT analysis, and the analysis of problems identified in the documentation stage to determine those that needs to be addressed. Lastly, recommendations, including implementation guidelines are proposed as solutions to the identified problems. During the documentation and problem analysis stages, the company fails to meet a significant 35% of the orders that the company receives on the average because of the stock out of the major raw materials and an inefficient current distribution system. To address this, improving the present distribution system and increasing the production volume are proposed. Recommendations with respect to minimizing the number of undelivered orders by reviewing the scheduling of deliveries and the preventive maintenance of the trucks used are made. With respect to increasing the production volume of the company's line of products, the solutions include improving the efficiency of the production technology used, streamlining the materials management and production planning procedures of the company, and improving the efficiency of the current facilities by adopting facilities planning and improving the working conditions in the shop floor. The concept of improving the waste management and raw material usage conservation practices of the company is also included in the recommendations. The result of addressing the identified problems is a set of short-term as well as long-term plans of action for the company. These plans of action ultimately aim to generate greater profit for the company to improve its position in the industry for the next 10 years or more. This time frame refers to that span of time that the company expects to have an abundant and cheap supply of wood, which is the primary raw material for the continuing production of the company's products. The management realizes that in the future, they have to divert all its resources to another unrelated business to continue operating profitably, due to the inevitable declining supply and increasing cost of wood.